Political Representation as Collective Representation. Considerations Based on the Brazilian Case. Issue 3 (3rd July 2019) - Ricci, Paolo
ABSTRACT: Scholars of electoral democracy and democratisation have tended to map political representation onto a relationship between individuals. In this article I introduce the concept of collective representation in order to encapsulate the idea that in the nineteenth century and, to a lesser extent, at the start of the twentieth, voting was a collective rather than individual act. I investigate whether the transition to a modern form of representation—denominated individual representation —took place with the protection of individual freedom. The secret ballot and combatting electoral fraud comprise the two dimensions of freedom that explain this transition. The case of Brazil—a country that initially presents the characteristics of collective representation and adopts a series of electoral reforms that provide the incentives for the transition to individual representation to occur—provides the preliminary basis for showing that this transition is not automatic and that we need to take into account the capacity of elites to adapt to changes in the electoral rules. This new form of thinking about political representation has important theoretical and empirical implications for scholars of democracy.